1993
DOI: 10.1007/bf00005471
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wastewater treatment plant effluents on freshwater mollusks in the upper Clinch River, Virginia, USA

Abstract: Field and laboratory studies were conducted to determine mollusk distributions in proximity to wastewater treatment plants (WTP's) in the upper Clinch River and to test the tolerance of two mollusk species to monochloramine and unionized ammonia, the major toxicants in domestic effluent. River reaches up to 3.7 km downstream of WTP's were devoid of freshwater mussels (Unionidae), and tolerance to effluents varied among snails, sphaeriid clams, and the asian clam CorbiculaJEuminea. Residential communities with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 34 publications
2
70
5
Order By: Relevance
“…Movement of anthropogenic nutrients into the food web was also documented in headwater streams in the Piedmont of NC [170,171]. In VA, freshwater mussels were absent below a wastewater treatment plant, most likely due to sensitivity to the domestic effluent; however, snails and clams were more tolerant [172]. As wastewater treatment plants are often embedded in the urban landscape, it can be difficult to tease apart the most significant factor causing reduced ecosystem health.…”
Section: Urbanization Effects On Biological Communitiesmentioning
confidence: 99%
“…Movement of anthropogenic nutrients into the food web was also documented in headwater streams in the Piedmont of NC [170,171]. In VA, freshwater mussels were absent below a wastewater treatment plant, most likely due to sensitivity to the domestic effluent; however, snails and clams were more tolerant [172]. As wastewater treatment plants are often embedded in the urban landscape, it can be difficult to tease apart the most significant factor causing reduced ecosystem health.…”
Section: Urbanization Effects On Biological Communitiesmentioning
confidence: 99%
“…Several lines of evidence point to the importance of various land use activities and riparian corridor integrity as determinants of native mussel and fish distribution in the Clinch and Powell River Basin with proximity to coal mining operations having the most adverse effects. Site-specific factors that could have also contributed to effects on IBI and mussel species richness are wastewater discharge and other point and nonpoint sources that could release toxic constituents or excessive nutrients downstream (47). Many of these were not explicitly included in our analyses due to a lack of appropriate data.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that unionids were often absent from large (*4 km) reaches below wastewater treatment facilities. Based on laboratory toxicity assays, Goudreau et al (1993) hypothesized that glochidial sensitivity to monochloroamine and unionized ammonia may be responsible for mussel extirpations downstream of wastewater outflows.…”
Section: Introductionmentioning
confidence: 99%
“…They found that although physicochemical conditions were not acutely toxic to mussels, large sections of the study river were devoid of mussels downstream of the effluent discharge. Goudreau et al (1993) examined effects of wastewater discharge on mollusk assemblages in the Clinch River in Virginia, USA. They reported that unionids were often absent from large (*4 km) reaches below wastewater treatment facilities.…”
Section: Introductionmentioning
confidence: 99%